2022
DOI: 10.1186/s12968-022-00874-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural reverse myocardial remodeling following transcatheter aortic valve replacement: a prospective cardiovascular magnetic resonance study

Abstract: Background Since cardiovascular magnetic resonance (CMR) imaging allows comprehensive quantification of both myocardial function and structure we aimed to assess myocardial remodeling processes in patients with severe aortic stenosis (AS) undergoing transcatheter aortic valve replacement (TAVR). Methods CMR imaging was performed in 40 patients with severe AS before and 1 year after TAVR. Image analyses comprised assessments of myocardial volumes, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Consistent with these findings, a multicentre, observational, outcome study with imaging core‐lab analysis of 674 patients with severe AS, LGE on CMR before SAVR or TAVI was independently associated with all‐cause mortality 42 . On the other hand, ECV is associated with myocardial functional recovery from HF following TAVI 41 . Additionally, electrocardiographic strain pattern (ESP) is a relevant marker of myocardial fibrosis that is associated with an increased risk of CV morbidity and mortality in asymptomatic AS and SAVR patients.…”
Section: Clinical Factors Associated With Heart Failure Hospitalizati...mentioning
confidence: 62%
See 1 more Smart Citation
“…Consistent with these findings, a multicentre, observational, outcome study with imaging core‐lab analysis of 674 patients with severe AS, LGE on CMR before SAVR or TAVI was independently associated with all‐cause mortality 42 . On the other hand, ECV is associated with myocardial functional recovery from HF following TAVI 41 . Additionally, electrocardiographic strain pattern (ESP) is a relevant marker of myocardial fibrosis that is associated with an increased risk of CV morbidity and mortality in asymptomatic AS and SAVR patients.…”
Section: Clinical Factors Associated With Heart Failure Hospitalizati...mentioning
confidence: 62%
“…It is important to note that the prognosis of patients with AS after valve replacement may not solely depend on improved flow dynamics but rather on the extent of irreversible myocardial fibrosis during the remodelling phase that occurs before the intervention 39 . Myocardial fibrosis can be divided in two categories: diffuse fibrosis occurs in the early phase of the disease, is potentially reversible, and can be quantified as extracellular volume (ECV) with CMR T1 mapping techniques, whereas replacement fibrosis is irreversible and can be identified using late gadolinium enhancement (LGE) on CMR 39–41 . Consistent with these findings, a multicentre, observational, outcome study with imaging core‐lab analysis of 674 patients with severe AS, LGE on CMR before SAVR or TAVI was independently associated with all‐cause mortality 42 .…”
Section: Clinical Factors Associated With Heart Failure Hospitalizati...mentioning
confidence: 74%
“…However, cardiac magnetic resonance scans as an alternative also are accompanied by advantages and disadvantages such as software‐specific native T1 times and differing normal values 37 . Furthermore, in the absence of follow‐up examinations, we are unable to report on reverse remodelling in regard to AVC and MF 38 . Finally, our study included Medtronic CoreValve and the Edwards SAPIEN 3™ valves, which were standard devices at the time of data collection.…”
Section: Discussionmentioning
confidence: 99%
“…37 Furthermore, in the absence of follow-up examinations, we are unable to report on reverse remodelling in regard to AVC and MF. 38 Finally, our study included Medtronic CoreValve and the Edwards SAPIEN 3 ™ valves, which were standard devices at the time of data collection.…”
Section: Limitationsmentioning
confidence: 99%
“…Lange et al reported that not only hypertrophic cardiomyocytes but also some fibrotic tissue associated with LVH due to severe AS recover after TAVR. 26 Such histological reversibility may be associated with recovery of CSN function after TAVR. CSN dysfunction is known to be a poor prognostic factor in patients with heart failure.…”
Section: Left Ventricular Hypertrophy and Cardiac Sympathetic Nerve D...mentioning
confidence: 99%